Anomalous anisotropic magnetoresistance in epitaxial Fe3O4 thin films on MgO (100) - SHVETS, IGOR (American Physical Society, 2008)
Studies of the angular dependence of the anisotropic magnetoresistance (AMR) are reported for epitaxial films of magnetite (Fe3O4) grown on MgO(001) and also for single crystals of magnetite. The characteristic feature of the AMR is a twofold symmetry at temperatures above 200 K. As the samples are cooled below 200 K, an additional set of peaks appears. These become dominant at lower temperatures showing an overall fourfold symmetry. Observation of additional anisotropy in the AMR points to formation of charge ordering at much greater temperatures than the Verwey transition temperature and is possibly related to the polaron formation in magnetite.
PUBLISHED
Keywords: magnetite; magnetoresistance